Impact of Physical Work Environment upon Nurses’ Job Performance in Hospitals - Kadhim, Hussein; Qassem, Wissam Jabbar (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To assess the physical work environment in hospitals; to evaluate nurses’ job performance in those hospitals, and to determine the impact of physical work environment upon nurses’ job performance.Methodology: A descriptive analytical study was designed and carried out during the period from May 15, 2022 to 1 January, 2023 in Nasiriyah City/Iraq. Non-probability (purposive) sample of (410) nurses working in the city center hospitals were selected for the purpose of the study. A questionnaire was designed and constructed to measure the variables through the review of literature and related studies. Content validity is determined by a panel of (8) experts of faculty members. Internal consistency reliability through Pearson correlation coefficient was r= 0.82. Data collection process is preformed through the use of the study questionnaire and data are analyzed through using the program of Statistical Package of Social Sciences (SPSS, Version 21).Results: The data analysis revealed that those nurses are working in an inappropriate work environment and they are at risk for exposing to health problems. Regarding their job performance all the sub domains’ items shows low level of job performance, and there was a great impact from the work environment upon their job performance.Conclusion: The study concluded that there was a great impact of the physical work environment upon nurses’ job performance.Recommendations: The study recommends for continuous work environment monitoring in Nasiriyah City hospitals, and regular medical examinations should also be initiated for those nurses for early detection and diseases protection from environmental risks potentials.